Immersive media practices in the classroom: models of the teaching research nexus in an Australian context. Issue 4 (1st October 2020) - Dooley, Kath; Bender, Stuart; Ferris, Gregory; Frankham, Bettina; Munt, Alex; Schleser, Max
ABSTRACT: In recent years, a new wave of virtual reality (VR) and immersive media forms have gained popularity with both viewers and creators around the globe. This article presents the argument that the emerging nature of this current wave of practices makes this a site of particular importance for research by both academics and students. We explore the nature of the teaching-research nexus around immersivemedia practices by reporting on six case studies from three Australian Universities. Academic experience is varied and complex, with avariety of Inquiry-based learning approaches in place at undergraduate and postgraduate level, spanning the areas of writing, production, post-production and spectatorship. A study of these aspects allows students to seek knowledge and new understandings of media forms, an experience that we believe is vital for the development of higher-order skills. By exploring this area, we pose the question: How canimmersive media researchers use Inquiry-based learning to conceptually engage students with emerging formats through course workdesign? Furthermore, we seek to examine how Inquiry-based learning in the context of immersive media connects to the more widely used Problem-Based Learning models that have traditionally been employed in media practice courses.